Effect of heat preservation time on the micro morphology and field emission properties of La-doped SiC nanowires. Issue 26 (18th June 2019) - Li, Weidong; Zhang, Meng; Li, Yu; Liu, Guangxia; Li, Zhenjiang
Abstract : Lanthanum doped SiC nanowires (La-doped SiC NWs) were prepared using the chemical vapor reaction technique at different heat preservation times. Abstract : Lanthanum doped SiC nanowires (La-doped SiC NWs) were prepared using the chemical vapor reaction technique at different heat preservation times. Polycarbosilane was employed as a provider of both the Si and C elements. The characterization results suggested that the products were β-SiC. The nanowires straightened, the diameter of the nanowires became larger, and the content of La reduced with increasing heat preservation time. Meanwhile, the coating layer of SiO2 obviously dwindled. The XPS spectrogram revealed that the existence of the element La in the product was in the form of a trivalent ion, La 3+ . The forbidden band width dropped from 1.37 to 0.8 eV after doping with La, which was calculated using Material Studio 4.2 software. When a heat preservation time of 120 min was used, the content of La had a minimum of 0.87 at%, and the turn-on field and the threshold field of the product were 1.2 and 5.0 V μm −1, respectively. A synergetic influence mechanism was put forward to explain the effects of the morphology and the La content on the field emission (FE) properties of the La-doped SiC NWs. This work could act as a reference article for those researching FE properties of other one-dimensional nano-materials.